PERAN BIMBINGAN BELAJAR DALAM PEMBENTUKAN SIKAP KEMANDIRIAN SISWA KELAS V SDN SINDANGSARI III - Riyo Gilang Ardhiansyah; Aam Amaliyah; Ahmad Amarullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines two variables: tutoring and the development of students' independent learning attitudes. The population of this study was all fifth-grade students at SDN Sindangsari III, Pasarkemis District, Tangerang Regency. Because the population was less than 100, this study selected 59 fifth-grade students from SDN Sindangsari III, Pasarkemis District, Tangerang Regency. A total of 10 students were sampled. The method used was descriptive qualitative research. This study used questionnaires and interviews. The results showed that the questionnaires distributed to fifth-grade students showed a score of 0.9351 out of 59 students, while the teacher interviews showed a score of 3.160. This means that the instrument for student independence and tutoring is significant.